Leverage asset pricing - Tobias Adrian; Emanuel Moench; Hyun Song Shin (Federal Reserve Bank of New York, 2013)
We investigate intermediary asset pricing theories empirically and find strong support for models that have intermediary leverage as the relevant state variable. A parsimonious model that uses detrended dealer leverage as a price-of-risk variable, and innovations to dealer leverage as a pricing factor, is shown to perform well in time series and cross-sectional tests of a wide variety of equity and bond portfolios. The model outperforms alternative specifications of intermediary pricing models that use intermediary net worth as a state variable, and it performs well in comparison to benchmark asset pricing models. We draw implications for macroeconomic modeling.
Keywords: G10; G12; 330; return predictability; cross-sectional asset pricing; financial intermediation; macrofinance